A Route for the Total Synthesis of Enantiomerically Enriched Jasmonates 12‐COOH‐JA and 12‐COOH‐JA‐Ile. Issue 5 (22nd December 2014) - Heinrich, Clément F.; Widemann, Emilie; Sanz, Jérémie; Lugan, Raphaël; Heitz, Thierry; Pinot, Franck; Miesch, Michel; Miesch, Laurence
Abstract: Enantiomerically enriched oxidized conjugated or non‐conjugated jasmonate derivatives were obtained through 3‐alkynoates. Stereoselective reduction of the triple bond afforded exclusively the Z isomer. Protection of the amide function led to the non‐conjugated derivatives, whereas the free amides provided the oxidized isoleucine derivatives of jasmonate. Abstract : A new synthetic route for enantiomerically enriched 12‐COOH‐JA and 12‐COOH‐JA‐Ile from (+)‐jasmonic acid is described. Ozonolysis afforded corresponding aldehydes that could be converted into 3‐alkynoates. Z ‐Stereoselective reduction of the triple bond gave the desired compounds. N ‐ tert ‐Butoxycarboxamide derivatives led to non‐conjugated 12‐COOH‐JA, whereas free amides provided 12‐COOH‐JA‐Ile.